Teaching mathematics to students with Down syndrome in the basic stage in Palestine in the light of some experimental studies and contemporary trends - Albustami, Salam Radi; Sulaye, Yaman Muaid (Journal of Educational and Psychological Sciences, 2021)
This study aimed to find mechanisms, methods, and strategies that should be considered in teaching mathematics to students with Down syndrome. The study relied on the descriptive approach, as it focused on theoretical literature and previous studies related to the topic. The study concluded that the process of teaching mathematics derives from the strategy based on the transition from perceived to abstract, and the process of teaching mathematics passes through three stages, the first of which is the sensory stage, which depends on the tools that the child can pick up and touch, then the semi-sensory stage and includes pictures and drawings related to reality and close to the environment Child, ending with the abstract phase based on the use of symbols. The study also found the ability of Down syndrome students to learn many basic math skills and concepts such as the skill of classification, counting, addition and subtraction, the study also found that the success of Down syndrome education methods depends on the teacher’s understanding of the lesson plan, the teacher’s ability to segment each goal into simple sub-goals, and reliance primarily on the strengths of Down syndrome students. It also indicated that teachers must consider the characteristics of students with Down syndrome, and choose the methods that are appropriate with their characteristics and their abilities, and necessity The teacher’s application of various methods in evaluating students in proportion to the individual differences between them, and the selection of methods that fit these characteristics and abilities that they achieve the best possible learning, and in a way that achieves psychological and social compatibility, and provide them with life skills that facilitates’ engaging in working life, independence and self-reliance.
Keywords: Teaching mathematics; Down syndrome; The primary stage; Disability